Ravens breeding in Warsaw in the 21th century - Zawadzki, Grzegorz; Jackowiak, Mateusz; Zawadzka, Dorota (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
In 2021, after a 65-year interruption, the Raven "Corvus corax" was found nesting again in the Royal Baths Park in central Warsaw, Poland. In addition, from 2021 to 2022, eight certainly or probably occupied breeding territories were found in forests and parks in the peripheral zone within the administrative borders of Warsaw. The synurbanization of the Raven in Warsaw is slow, as in other large Polish cities.
Keywords: wróblowe; ornitologia